Strategi Pengembangan Industri Kecil di Kota Bitung dengan Menggunakan Analisis SWOT dan Strategi TOWS - Stanny Sicilia Rawung; Maya F. S. Salindeho (Society, 2020)
-This study aims to analyze industrial groups’ position based on developing and business success and strategies that can be used in developing small-scale industrial enterprises in the Bitung City, North Sulawesi Province. The research took place in Bitung City, North Sulawesi Province. The research sample was 185 small business owners in Bitung City. The sampling method used was random. Data were collected using a questionnaire with a Likert scale and strategy analysis using SWOT analysis and TOWS strategy. The results of this study found that: (1) based on the SWOT analysis results, each industry group is advised to implement a survival strategy and future integration that is offered according to internal factors and external factors that affect the success of micro-businesses in Bitung City. (2) the small-scale industries in Bitung City have excellent development capabilities and a high business success level.